Percutaneous transvenous embolization for portosystemic shunts associated with encephalopathy: Long‐term outcomes in 14 patients. Issue 7 (11th July 2013) - Naeshiro, Noriaki; Kakizawa, Hideaki; Aikata, Hiroshi; Kan, Hiromi; Fujino, Hatsue; Fukuhara, Takayuki; Kobayashi, Tomoki; Honda, Yohji; Miyaki, Daisuke; Kawaoka, Tomokazu; Tsuge, Masataka; Hiramatsu, Akira; et al.
<x xml:space="preserve">Abstract</x> Aim To evaluate the clinical outcomes of percutaneous transvenous embolization (PTE) for portosystemic shunt (PSS) associated with encephalopathy Methods Fourteen patients with portosystemic encephalopathy (PSE) were enrolled in this retrospective cohort study. We evaluated technical success, clinical success, complication and outcomes. Results In cases in which PSS was one of main causes of PSE, three also had splenorenal shunts, four gastrorenal shunts, four superior mesenteric vein systemic shunts, one inferior mesenteric vein systemic shunt and two main trunk of portal vein inferior vena cava shunts. We used only ethanolamine oleate (EO) in five; EO and coils in five; EO, coils and n‐butyl 2‐cyanoacrylate (NBCA) in two; and coils and NBCA in two patients as embolic materials. The rate of primary and secondary technical success was 93% (13/14 patients) and 100%, respectively. No major complications were encountered related to PTE. Follow‐up period was a median of 27 months (range, 12–79). All patients had sustained disappearance of PSE. PSE recurred in one patient because of another PSS development. Thus, clinical success was achieved in 93% (13/14 patients). The ammonia levels 1 year after PTE were significantly improved compared with pre‐PTE (median, 102 vs 41 μmol/L) and maintained lower levels 2 and 3 years later. Child–Pugh scores did not change significantly. Esophageal varices were aggravated in 29% (4/14 patients). Five patients died, but no death of hepatic failure related to PTE was encountered. Conclusion PTE could be one of the useful treatment options for PSE.